High-intensity exercise training enhances mitochondrial oxidative phosphorylation efficiency in a temperature-dependent manner in human skeletal muscle: implications for exercise performance - Fiorenza, M.; Lemminger, A. K.; Marker, M.; Eibye, K.; Iaia, F. M.; Bangsbo, J.; Hostrup, M. (The FASEB Journal, 2019)
The purpose of the present study was to investigate whether exercise training-induced adaptations in human skeletal muscle mitochondrial bioenergetics are magnified under thermal conditions resembling sustained intense contractile activity and whether training-induced changes in mitochondrial oxidative phosphorylation (OXPHOS) efficiency influence exercise efficiency. Twenty healthy men performed 6 wk of high-intensity exercise training [i.e., speed endurance training (SET; n = 10)], or maintained their usual lifestyle (n = 10). Before and after the intervention, mitochondrial respiratory function was determined ex vivo in permeabilized muscle fibers under experimentally-induced normothermia (35°C) and hyperthermia (40°C) mimicking in vivo muscle temperature at rest and during intense exercise, respectively. In addition, activity and content of muscle mitochondrial enzymes and proteins were quantified. Exercising muscle efficiency was determined in vivo by measurements of leg hemodynamics and blood parameters during one-legged knee-extensor exercise. SET enhanced maximal OXPHOS capacity and OXPHOS efficiency at 40°C, but not at 35°C, and attenuated hyperthermia-induced decline in OXPHOS efficiency. Furthermore, SET increased expression of markers of mitochondrial content and up-regulated content of MFN2, DRP1, and ANT1. Also, SET improved exercise efficiency and capacity. These findings indicate that muscle mitochondrial bioenergetics adapts to high-intensity exercise training in a temperature-dependent manner and that enhancements in mitochondrial OXPHOS efficiency may contribute to improving exercise performance.